(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The present paper entitled “Female Genital Mutilation: The Infliction of Psychological and Sexual Trauma on Women in Alice Walker’s Possessing the Secret of Joy” intend to investigate the problems experienced by women after mutilation. Female Genital Mutilation or circumcision is a ritual of cutting or removing some or all of the external female genitalia. It is a topic of universal interest practised in many countries. Alice Walker, in her novel, Possessing the Secret of Joy, presents a fictional character Tashi, who is the protagonist of this novel and faces eternal conflicts after circumcision. Alice Walker also discusses Post Traumatic Stress Disorder (PTSD) in this novel. The present paper focuses on how the life of women shattered after undergoing this evil practice, which is socially constructed and has no medical reason but is performed only based on some myths. The primary objective of this paper is to highlight the harmful effects of female circumcision, which includes many severe physical and psychological issues that drag women into a traumatic disorder. This paper aims to reveal how this inhumane praxis oppresses women in the name of culture, how a woman is mangled for her whole life, and her life is spoiled. The conclusion of this research paper conceals that we can eradicate this praxis through knowledge and consciousness, which is attained only through feminist debates that will be helpful for women to put an end to such barbaric praxis.